ANALISIS KEMAMPUAN MENULIS KALIMAT MAJEMUK SISWA KELAS VI SD NEGERI 105 PEKANBARU - Munira Hayati; Otang Kurniaman; Zufriady Zufriady (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the problem of students not being able to place precisely the conjunctions in writing compoundsentences, and students have not been able to make compound sentences according to subject criteria, prediction, objects,and information. The purpose of this study was to describe the ability of sixth grade students of SD Negeri 105 Pekanbaru towrite compound sentences. This research has been carried out in July 2018 which uses descriptive quantitative methods withresearch subjects consisting of 142 students. Data collection techniques use test techniques, by giving 10 questions of essayquestions as an instrument. The results of the ability to write compound sentences for grade VI students from 142 studentsshowed 47 students who were categorized as very capable with a percentage of 33.09%, 22 students who were able to get acategory with a percentage of 15.50%, 34 students got enough categories with percentages 23.94% and 39 students got theless category with a percentage of 27.46%. Overall, the sample of 142 students obtained an average score of 67.61 in thecategory of quite capable. This shows that the ability to write compound sentences for students in grade VI of SD Negeri 105Pekanbaru as a whole has been categorized as quite capable.